3)
The first term is 35 and it keeps getting subtracted by 30 to get the other terms so this is the common difference, so we can write:
[tex]\sf a_n = a_{n-1}-30[/tex]
[tex]\sf a_1=35[/tex]
4)
The first term is 5 and it keeps getting subtracted by 8 to get the other terms so this is the common difference, so we can write:
[tex]\sf a_n = a_{n-1}-8[/tex]
[tex]\sf a_1=5[/tex]
5)
The first term is -29 and it keeps getting added by 200 to get the other terms so this is the common difference, so we can write:
[tex]\sf a_n = a_{n-1}+200[/tex]
[tex]\sf a_1=-29[/tex]
6)
The first term is 11 and it keeps getting added by 100 to get the other terms so this is the common difference, so we can write:
[tex]\sf a_n = a_{n-1}+100[/tex]
[tex]\sf a_1=11[/tex]
7)
The first term is 37 and it keeps getting added by 30 to get the other terms so this is the common difference, so we can write:
[tex]\sf a_n = a_{n-1}+30[/tex]
[tex]\sf a_1=37[/tex]
8)
The first term is 20 and it keeps getting subtracted by 6 to get the other terms so this is the common difference, so we can write:
[tex]\sf a_n = a_{n-1}-6[/tex]
[tex]\sf a_1=20[/tex]